College Choice…Holistic Development…Career Success…College Choice: Introducing the “Lifetime Human Capital Cycle” for Intercollegiate Athletes - Landon T. Huffman; Kristina M. Navarro; Coyte G. Cooper (Journal of Applied Sports Management, 2016)
The purpose of this article was to examine the college-choice factors of intercollegiate football athletes who were offered an athletic grant-in-aid to attend a NCAA Division I FBS university in the southeastern United States (n = 74). A modified version of the Student–athlete College-Choice Profile (SACCP) was used to collect data regarding the most influential college-choice factors. The questionnaire concluded with an open-ended question asking players to identify the three most-influential factors related to their college choice. A mixed-methods approach utilized descriptive statistics complemented by qualitative analysis techniques including process coding, pattern coding, and analytic memoing to identify the most influential college-choice factors and themes. The theoretical framework of Lifetime Human Capital was used to explain preferences in college selection. Lifetime Human Capital is the concept that recruits will select the college that will maximize their lifetime net worth after weighing the total benefits and costs. Participants indicated “Opportunity to begin a good career other than playing professional football” was the most influential factor in their college recruitment, which coincided with the theme of career development. Researchers used results from this study to construct the “Lifetime Human Capital Cycle” to illustrate the value and rationale for investing in holistic development programs.
Keywords: student-athlete recruitment; career development